IMPLEMENTASI METODE GALLERY WALK DALAM MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS VII DI SMPN 4 MADIUN - Aisyahtin Choirul Kholifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Student activeness is an important factor in learning success, yet in Pancasila Education learning for grade VII of SMPN 4 Madiun, some students were still found to be less active in asking questions, discussing, and expressing opinions. This study aims to describe the implementation of the Gallery Walk method in increasing student activeness in Pancasila Education learning for grade VII of SMPN 4 Madiun. This study used Classroom Action Research (CAR) with grade VII students as subjects, with data collected through observation, documentation, and learning reflection, then analyzed descriptively and qualitatively. The results show that the Gallery Walk method was able to increase student activeness through discussion, observation of group work, giving responses, and presentation, making learning more interactive and collaborative.